2002
DOI: 10.1002/aic.690480318
|View full text |Cite
|
Sign up to set email alerts
|

Formation and dynamics of a hot zone in radial flow reactor

Abstract: An infrared camera was used to study the formation and dynamics of hot zones

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 22 publications
(12 reference statements)
1
28
0
Order By: Relevance
“…Using a regularized low dimensional model, our previous works [1, 2, 3] mainly focused on the symmetric patterns that develop due to the difference in mixing and reaction time scales, while our present paper simulates the formation of asymmetric patterns, which have been observed in experimental studies [4]. We find that higher eigen modes of initial perturbation lead to patterns that are more stable and more asymmetric than those formed from lower modes.…”
mentioning
confidence: 49%
See 1 more Smart Citation
“…Using a regularized low dimensional model, our previous works [1, 2, 3] mainly focused on the symmetric patterns that develop due to the difference in mixing and reaction time scales, while our present paper simulates the formation of asymmetric patterns, which have been observed in experimental studies [4]. We find that higher eigen modes of initial perturbation lead to patterns that are more stable and more asymmetric than those formed from lower modes.…”
mentioning
confidence: 49%
“…The formation of patterned states may often reduce the product yield by deactivation of the catalyst or reactor runaway. Using a regularized low dimensional model, our previous works [1,2,3] focused on the symmetric patterns that develop due to the difference in mixing and reaction time scales, while our present paper simulates the formation of asymmetric patterns, typically observed in experimental studies [4].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous experiments with a shallow radial flow reactor (Marwaha et al, 2001;Marwaha and Luss, 2002) revealed breathing motions, while experiments in a shallow packed bed (Marwaha and Luss, 2003) showed that in addition a splitting and recombination of the hot zone may occur. The current experiments, using smaller (2-3 mm) diameter pellets, revealed a much richer and complex dynamics than when using larger (3-4 mm) diameter pellets.…”
Section: Discussionmentioning
confidence: 97%
“…[9,10]. Such a condition can often decrease the yield of the desired product, deactivate the catalyst, initiate highly exothermic undesirable reactions or induce safety hazards by decreasing the reactor strength.…”
Section: Introductionmentioning
confidence: 97%